Hand-Arm Vibration Syndrome in Dentistry: A Questionnaire Survey among Dentists and Review of Literature - Alice Turcot; Denis Hamel; Mélanie Tessier (Proceedings, 2023)
The use of dental handpieces and ultrasonic instruments expose dental professionals to high-frequency vibration, precise gripping, high pinch force, and repetitive bending movements of wrist during restorative procedures involving cutting dental material, periodontal scaling, and root planning. There is clear evidence of an association between the dentistry profession and work-related musculoskeletal disorders in the neck, upper back and upper extremities; however, the influence of high-frequency vibration on hand and fingers from dental handpieces is not well known. The objectives of the current paper are to present the results of a survey on hand-arm vibration syndrome (HAVS) among members of a professional dental society and to present a literature review on dental handpieces and ultrasonic scalers exposure assessment and occurrence of hand-arm vibration syndrome among dental professionals. There seems to be limited awareness of the occupational risk associated with hand-arm vibration from handpieces and ultrasonic devices. This study highlights the occurrence of vascular and neurological disorders of HAVS among dental professionals, as well as wrist/hand pain, osteoarthritis, diminished hand grip, and carpal tunnel syndrome. The assessment of high-frequency vibration and ultra-vibration from these vibrating tools and vibration-related injuries deserve special attention for future preventive measures.